Krisis ekonomi Asia Timur : komentar dan analisis - Khor, Kok Peng (Pulau Pinang : Persatuan Pengguna Pulau Pinang, 1998)
Globalization and the economic crises in Asia; collection of articles
In Malay
Keywords: Financial crises -- Asia; Globalization; Asia -- Foreign economic relations